MEDIA RELATIONS IN MAINTAINING INSTITUTIONAL REPUTATION OF THE WEST SUMATERA REGIONAL POLICE - Selvia Maharani; Elva Ronaning Roem; Ilham Havifi (Universitas Negeri Medan, 2025)
Media relations is a central function of public relations aimed at building productive relationships with mass media to support accurate and timely information dissemination. The West Sumatra Regional Police (Polda Sumbar) has faced negative news coverage that influenced its institutional reputation, prompting its Public Relations Division to strengthen media relations practices. This study examines how Polda Sumbar implements media relations as a reputation management strategy in the context of increasingly dynamic digital media. A descriptive qualitative approach was employed within a post-positivist paradigm. Data were collected through in-depth interviews, observations, and document analysis, and were analyzed using the Miles, Huberman, and Saldana model. J.E. Grunig’s Excellence Theory in Public Relations was used to understand the type of communication and relationship developed between Polda Sumbar and the media. The findings show that Polda Sumbar applies several media relations strategies, including organizing press conferences, utilizing digital communication groups, providing information verification services, and conducting informal interactions with journalists to strengthen interpersonal rapport. These practices reflect two-way symmetrical communication characterized by openness, responsiveness, trust-building, and collaboration. The institution also performs continuous media monitoring and evaluation to anticipate emerging issues that may threaten its reputation. The study concludes that media relations serve as a strategic tool for sustaining institutional reputation, enhancing public trust, and supporting organizational accountability. It recommends strengthening public relations competencies and optimizing digital communication to ensure more effective and sustainable media relations practices in the future. Key words: Communication, Maintaining, Media Relations, Polda Sumbar, Reputation